E-Modul Fisika Berbasis Contextual Teaching and Learning Menggunakan Aplikasi Kvisoft Flipbook Maker Untuk Meningkatkan Literasi Sains Peserta Didik SMA/MA Kelas XI - Nurhasnah, Nurhasnah; Sari, Liza Ayuna (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This research is motivated by the low ability of scientific literacy of students. One of the causes of students 'low scientific literacy skills is the lack of teaching materials that can shape students' scientific literacy skills. The available teaching materials have limitations to illustrate the facts of the lessons learned in everyday life. The type of research used is research and development with the ADDIE design model (Analysis, Design, Development, Implementation, Evaluate). Based on research and analysis of CTL-based e-module data using Kvisoft Flipbook Maker on the ability of scientific literacy, namely: obtain an average value of 4 people validator 88% with a very valid category. practicality assessment of 2 physics educators was 79.33% with a practical category. Practical assessment of 15 students received an average value of 90.26% in the category of very practical, has an average value of 84.79% with a very practical category. Assessment of the effectiveness of scientific literacy of 15 students for e-learning modules in the questionnaire obtained an average value of 88.78% with a very effective category while the test questions on the kinetic theory of gas with 66.6% completeness and in the material thermodynamics with 64.8% completeness with an average value of 65.7%. So it can be concluded that e-module based on Contextual Teaching And Learning (CTL) using Kvisoft Flipbook Maker on the kinetic theory of gas and thermodynamics is very valid, practical and effective to improve science literacy in physics learning class XI MIPA 6 SMA N 15 Padang